Molly eaudiobook American girl 1944. - Tripp, Valerie (American Girl: Molly., 2008)
The Molly books from American Girl are delightful reads for young people. With a spunky and energetic heroine, exciting storylines set against the rich historical backdrop of World War II America, and important life lessons, the Molly books are modern children's classics that no library should be without.